Association of altered serum glucose and lipid profiles with headaches in young women: clinical, cross-sectional study - Zola, Karen Valério; da Silva , Jóvyne Karollyna Kaleski Vicente; Lima Filho, Jonas Bernardes; Ramos, Bruna Ribeiro Andrade; Pereira, Vinicius Coralino Dos Reis; Galli, Nilva; Orsatti, Claudio Lera (Headache Medicine, 2023)
Introduction Headaches, including migraines and tension headaches, affect millions of people globally. Migraines are the most common neurological disorder, with around 14.4% of the world's population affected. It is suggested that dysregulation of biochemical markers and individual metabolic differences may contribute to headaches. Objective We evaluated the frequency of headaches or migraines with changes in lipid, glucose and vitamin D serum levels in young women. Methods Clinical, cross-sectional study with 139 young women, aged at least 18 years, based on the third edition of the International Classification of Headache Disorders (ICHD-3). The individuals were divided into two groups: one without headache and another with headache. Anthropometric analyzes (BMI, WC, BP and DBP) and blood samples were collected for analysis of vitamin D, glycemia and lipid profile. Results Mean age was 22 (±4.6) years. We observed associations between headache and the following factors: high glucose levels (97 mg/dL, p=0.028), total cholesterol (180.4 mg/dL, p=0.002), HDL (44.2 mg/dL, p=0.017), and LDL (121.6 mg/dL, p=0.005). Longer duration of headache attacks was associated with increased levels of glucose (97.9 mg/dL, p=0.028), total cholesterol (186.8 mg/dL, p=0.05), diastolic blood pressure (74 mmHg, p=0.038), and BMI (24.6 kg/m2, p=0.024). High glucose levels were found to be directly related to the presence of migraine, particularly those with aura (105 mg/dL, p=0.034). However, there was no significant difference in vitamin D levels (p=0.640). Conclusion Elevated levels of blood glucose and total plasma cholesterol and its fractions seems to be associated can increase with bouts of headache attacks, especially migraine, prolonging the duration of pain.